Immigration: What about the Children and Grandchildren? - Arthur Sweetman; Jan C. van Ours (Institute for the Study of Labor (IZA), 2014)
Intergenerational immigrant integration is central to the economic growth and social development of many countries whose populations comprise a substantial share of the children and grandchildren of immigrants. In addition to basic demographics, relevant economic theories and institutional features are surveyed to assist in understanding these phenomena. Building on this foundation, educational and labor market success across the immigrant generations are reviewed, and then studies on the evolution of social outcomes across those same generations are discussed. Overall, substantial cross-national heterogeneity in outcomes is observed as various sources of immigration interact with distinct national labor markets and educational/social contexts that have diverse approaches to integrating immigrants.
Keywords: J15; 330; labor market position; educational attainment; 1.5-generation immigration; second-generation immigration; intergenerational assimilation; economic integration